2001
DOI: 10.1093/ps/80.7.874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age at Molting on Postmolting Performance

Abstract: Molt was induced at the 431, 501, or 571 d, in Lohmann (L) and Hy-Line W-77 (H) hens, by 8 or 14 d, respectively, of feed withdrawal followed by a rest period of 16 d. Induced molt resulted in increases in egg production, numbers of intact eggs, egg mass per housed or surviving hen, and shell quality and in decreases in egg breakage (not significant), mortality, and culling. Egg weight was only slightly affected by molt, and the EW of hens induced to molt at 431 or 501 d of age were slightly lower than those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
5
10
0
1
Order By: Relevance
“…These results confirm previous findings on the improvement in egg production and in shell quality after induction of an artificial moult by zinc oxide with or without restriction of light (Berry and Brake, 1987;Ramos et al, 1999;Bar et al, 2001). Garlich et al (1984) and Table 7.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm previous findings on the improvement in egg production and in shell quality after induction of an artificial moult by zinc oxide with or without restriction of light (Berry and Brake, 1987;Ramos et al, 1999;Bar et al, 2001). Garlich et al (1984) and Table 7.…”
Section: Discussionsupporting
confidence: 92%
“…The restorative effects of an induced moult on shell quality and the productivity of old laying hens is well substantiated (Berry and Brake, 1987;Bar et al, 2001). Thus, the aim of the current study was to explore the origin of the enhanced shell quality after moult and to use this model for establishing a possible relationship between the organic matrix components, shell microstructure and its mechanical properties.…”
Section: Introductionmentioning
confidence: 93%
“…Bar et al (2001) showed that induced moulting resulted in increases of egg production, egg mass per housed or surviving hen, numbers of intact eggs and shell quality. Alike Wu et al (2007) reported that hens moulted by feed withdrawal had significantly higher egg production and egg mass during the later stage of the post-moulting production period compared with hens moulted by no-salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…El desempeño productivo de las aves en el segundo ciclo, se comienza a evaluar con los días improductivos a partir de la aplicación del DO, lo cual indica que el período improductivo aumenta a medida que el ave envejece, que bien podría interpretarse como una menor velocidad de recuperación del tracto reproductivo del ave a medida que aumenta la edad, aspecto expresado por Bar (19), quien recomienda no realizar inducciones al DO en aves con una avanzada edad, ojalá con menos de 100 semanas de vida.…”
Section: Discussionunclassified